(untitled) (Journal of the College of Education for Women, 2019)
The process of cognitive representation includes mental activities such as perception, concepts formation and decision making leading to formation of Cognitive representation where the need for Cognition is one of basic humane needs promoting individuals to have more information.This Study aims to measure the level of Cognitive representation among gifted Schools, the level of need for Cognition among them, recognize statistical Significant differences with Cognitive representation according to gender Variable and recognize the Correlation between Cognitive representation and the need for Cognition among giftel schools . The sample Consists of subsample of mair application one Consisting of( 400) students, noting that the first sample which is the sample of building the scale differs from main application one, where the member male students was (200) and female ones was (200) whom Chosen randomly. The researcher Concludes Someof results:1- The individuals of the sample, according to the Comparison between arithmetic mean and hypothetical one, carachtrized with Cognitive representation at (0,05) level.2-The individuals of the sample, according to the Comparison between arithmetic mean and hypothetical one, have the need for cognition at 0,05,level3-There are no statistical significant differences on the scale of cognitive representation according to gender variable at (0,05) level.4-There are statistical significant differences on the scale of the need for cognition according to gender variable at (0,05) level.5- There is a correlation between the scale of cognitive representation and the scale of the need for cognition where it is (0,36) at (0,05) level.The researcher reaches to a unmber of Suggestions ,recommendations and Conclusions